Using six-word stories to trigger EFL learners’ creative writing skills - Phuong Le (Universitas Katolik Indonesia Atma Jaya, 2018)
There has been a growing volume of six-word stories and related literature available in recent decades. In only six words, the authors are able to tell amazing stories of various types, packed with strong emotions. Inspired by the succinct and thought-provoking language use of these stories, the author has used this valuable source of materials as prompts in promoting EFL learners’ creativity and language development, both at high school and tertiary levels in a semi-structured case study in Vietnam. The article illustrates the different language activities that have been used with two groups of EFL students and their related products. Implications are introduced for their applications in similar educational contexts.